MORAL VALUES IN ANTOINE DE SAINT EXUPERY’S THE LITTLE PRINCE - Oki Syahputra Waruwu; Sewistina Bu’ulolo; Ismarini Hutabarat (LPPM Universitas Darma Agung, 2023)
This thesis entitled is Moral Values ​​in Antoine De Saint Exupery's The Little Prince. This analysis is about the moral values ​​contained in the little prince character. In this thesis, the writer wants to show some of the moral values ​​that exist in the character of the little prince and show how the author describes each of the moral values ​​contained in the novella. To complete this analysis, the writer used Teori Pengkajian Fiksi by Nurgiyantoro,the writer also used qualitative research and conducts several analysis results on the library. As data analysis, the writer chose the novella The Little Prince (le petit prince) with the title Moral Values ​​in Antoine de saint exupery's The Little Prince. The results of this thesis, the writer found several moral values ​​namely responsibility, care, love and affection, politeness, friendship, loyalty, honestly and humility and the writerdescribe how the potrayed of moral values that have been found